An investigation of the open-system Bus Rapid Transit (BRT) network and property values: The case of Brisbane, Australia. (April 2020) - Zhang, Min; Yen, Barbara T.H.; Mulley, Corinne; Sipe, Neil
Abstract: This paper presents an investigation of the open-system Bus Rapid Transit (BRT) network on property values. An open-system BRT is one where bus feeder lines can enter and leave the BRT system, depending on their origin or destination so the BRT system infrastructure is shared by multiple routes. Brisbane, Australia is the empirical setting where smartcard (GoCard) data shows that 43% of bus passengers accessed the BRT system from feeder line stops. The paper investigates whether feeder line stops are important for increasing network accessibility in Brisbane's open-system BRT. The hypothesis underpinning the study is that the improved accessibility resulting from an open-system BRT network results in higher property values within feeder line corridors in addition to simply around the BRT system. A Geographically Weighted Generalized Linear Model (GWGLM) is used to investigate property value premiums and their spatial distribution. GWGLM makes an improvement over Geographically Weighted Regression Model (GWR) by providing flexible local and global variable settings that decrease the risk of multi-collinearity in local models. The results identify property value uplift of up to 1.64% for every 100 m closer to feeder bus stops with frequent services in western and eastern Brisbane suburbs. Future studies should pay attention to the type of BRT operation (whether open- or closed-) in investigating the value of accessibility from BRT implementation. The results are policy relevant for the debate between whether BRT systems should be open or closed.